Enhanced Photocatalytic Degradation of Methylene Blue by WO3 Nanoparticles Under NIR Light Irradiation - Yin, Xiuzhao; Liu, Lu; Ai, Fujin (Frontiers in Chemistry, 2021)
Photocatalysts have been paid great attention owing to their excellent performance in the degradation of dangerous organic pollutants. Herein, a novel longitudinally grown photocatalyst, WO3, was prepared by a traditional method using a hydrothermal process, which had strong ultraviolet, visible light absorption ，and weak near-infrared radiation (NIR) absorption. The produced WO3 photocatalyst exhibited excellent performance in the rapid degradation of methylene blue (MB) in industry. It has been proved that the photothermal effect is mainly responsible for the rapid degradation of MB under NIR laser irradiation loaded visible light. Besides, it has been found that different morphologies and structures affect the degradation of MB. The longitudinally grown enlarged the contact area between photocatalyst and MB, and expanded the scope of the absorption wavelength of light, enhancing the stability of photocatalytic materials. So this unique transverse longitudinal structure exhibited a potential capability for degrading organic pollutants in industry.